Women entrepreneurs and innovation: Retrospect and prospect - Michela Mari; Sara Poggesi; Gianpaolo Abatecola; Caroline Essers (Journal of Innovation & Knowledge (JIK), 2024)
This paper answers the call for a deeper understanding of innovation issues in relation to female entrepreneurship. In doing so, it offers a comprehensive and updated picture of the state of the art of management research on innovation in women-owned firms. Specifically, by conducting a systematic literature review, which is widely used in management studies, and by using rigorous and replicable criteria, this manuscript seeks to understand this crucial intersection through an in depth investigation of 48 papers, thus addressing a relevant gap that exists in literature to date. Results demonstrate that, despite the increasing attention given to female entrepreneurship and innovation at both political and social levels, due to their key role worldwide, a significant gap in the integration of these two areas still exists. Thus, it is time for scholars to reimagine the concept of innovation and to explore the untapped potential within female entrepreneurship, redefining and bringing to light all the facets that innovation may have. The study provides avenues on which scholars should focus in order to help policy makers to work towards fostering a more inclusive and dynamic entrepreneurial ecosystem that empowers women to drive innovation and economic growth.
Keywords: L26; 650; Women entrepreneurship; Gender; Innovation; Systematic literature review